2009
DOI: 10.1017/s0266462309990432
|View full text |Cite
|
Sign up to set email alerts
|

Self-report versus care provider registration of healthcare utilization: Impact on cost and cost-utility

Abstract: This study showed that the use of self-reported data or data from registrations effected within-group costs, but not between-group costs or the cost utility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
0
19
0
Order By: Relevance
“…Hoogendoorn et al compared self-report versus care provider registration of healthcare utilizations and its impact on cost and cost-utility. They found that the degree of under-reporting was independently associated with loss to follow-up and total costs, showing that those lost to follow-up had larger differences in costs between registrations and self-reports compared with full participants [27].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hoogendoorn et al compared self-report versus care provider registration of healthcare utilizations and its impact on cost and cost-utility. They found that the degree of under-reporting was independently associated with loss to follow-up and total costs, showing that those lost to follow-up had larger differences in costs between registrations and self-reports compared with full participants [27].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of that difference on, for example, cost-effectiveness studies should be taken into consideration. For example, Hoogendoorn et al found that despite the almost perfect agreement on hospitalizations and hospital days, the cost difference was highest for this type of care, approximately 390 euros [27].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Like other retrospective cost assessments, this study was prone to recall error regarding utilisation of healthcare services. As far as recall abilities of parents are not associated with their child’s exposure to tobacco smoke, this should only influence the estimated average costs, not the differences between groups [42,43]. Additionally, our results may not be fully representative for the German population with regard to health-related as well as socio-demographic characteristics.…”
Section: Discussionmentioning
confidence: 90%
“…9 Several studies have validated use of cost questionnaires for collection of the wide range of these patient expenses. 10,11,12,13 Table 3 is a list of definitions of non-reimbursed and out-of-pocket costs collected in this study. 14 …”
Section: Methodsmentioning
confidence: 99%